2013
DOI: 10.1111/jpn.12089
|View full text |Cite
|
Sign up to set email alerts
|

Forage and sugar in dairy calves' starter diet and their interaction on performance, weaning age and rumen fermentation

Abstract: The effects of sugar and forage inclusion in calves' starter and their interaction on animal performance and rumen fermentation parameters were investigated. Twenty-eight neonatal Holstein male calves 3 days of age with average body weights of 42 ± 4 kg were allocated to four different treatments. All calves were fed a similar basal diet consisting of milk and concentrate. The experimental treatments were: (i) basal diet with no supplementation (Control, hereafter designated by C), (ii) basal diet plus 5% gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 20 publications
1
4
0
1
Order By: Relevance
“…in other studies (Ghassemi Nejad et al, 2012;Terré et al, 2015;Mirzaei et al, 2016). Results of body measurements herein are in agreement with others, who found that most skeletal growth parameters were similar in calves supplemented with or without forage in starter diet (Beiranvand et al, 2014a;. However, in contrast to our results, it has been reported that heart girth and body barrel were lower (Maktabi et al, 2016) or higher (Daneshvar et al, 2015) in calves receiving AH compared with those not receiving hay.…”
Section: Discussionsupporting
confidence: 91%
“…in other studies (Ghassemi Nejad et al, 2012;Terré et al, 2015;Mirzaei et al, 2016). Results of body measurements herein are in agreement with others, who found that most skeletal growth parameters were similar in calves supplemented with or without forage in starter diet (Beiranvand et al, 2014a;. However, in contrast to our results, it has been reported that heart girth and body barrel were lower (Maktabi et al, 2016) or higher (Daneshvar et al, 2015) in calves receiving AH compared with those not receiving hay.…”
Section: Discussionsupporting
confidence: 91%
“…In the past 2 decades, studies reporting the addition of forages in the diets observed negative effects when preweaning calves were fed free-choice high-quality forages, such as chopped alfalfa hay (17% CP and 47% NDF), with forage intake up to 14% of the total DMI (Terré et al, 2013b). The high palatability of this forage may depress the concentrate intake, resulting in a replacement effect, due to the low intake capacity of young calves (Beiranvand et al, 2014). Feeding high-quality forages tends to result in a higher forage: concentrate ratio than when the straw is fed (Castells et al, 2012).…”
Section: Calf Intake and Growth Performancementioning
confidence: 99%
“…Chopped hay and starter can also be combined and provided as a mixture to promote more consistent hay intake. If mixing hay and calf starter increases solid feed intake, it also has the potential to influence the growth and development of the calf (Beiranvand et al, 2014a). However, no recommendation exists for how hay should be provided to young calves for optimal growth and development.…”
Section: Introductionmentioning
confidence: 99%